Reproducing Patriarchy in Malay-Jawi Exegesis: The Representation of Working Women in Tafsīr Nūr al-Iḥsān - Nisa Mardiyah, Nur Maliyah; Nor Syamimi Mohd (Journal of Ushuluddin and Islamic Thought, 2023)
The issue of women pursuing careers in the public sphere continues to be a subject of debate in contemporary social and academic circles. The stigma attached to career women not only reflects resistance to gender role change but also reproduces patriarchal discourse structures through religious authority. This study analyzes the construction of career women in Tafsīr Nūr al-Iḥsān by Sa‘īd b. ‘Umar Qāḍī using a qualitative-descriptive approach and an Islamic feminist framework. Data were obtained through literature review and unstructured interviews. The results of the analysis reveal three main ideas: (1) women are ontologically positioned as unequal to men; (2) women’s activities should be limited to the domestic sphere; and (3) women’s leadership is permitted on the condition of their husband’s consent and fulfillment of domestic roles. These findings suggest that the interpretation not only reflects traditional normative views but also functions as an ideological instrument in maintaining patriarchal gender structures. This study contributes to enriching Malay Jawi interpretation studies with a critical approach and opens new discourse in reading interpretations as an arena of contestation between tradition and gender emancipation in Southeast Asia.